Metode Istinbat Al Hukm Ibnu Hazm - Suchrulloh, Muchamad (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2024)
Istinbat is an attempt by a fuqaha' to explore Islamic law from its sources. The existence of a jurisprudence expert is very important considering that this is a series of paradigms that are used as marja' or parameters for him in exploring and establishing law. As was done by the fuqaha' Madhahib al-'Arba'ah in exploring a legal product from the Koran and Sunnah. So that what is the foundation of Madhahib al-'Arba'ah's opinions can be accepted by the wider community, who do not translate the Qur'an textually as was done by Ibn Hazm in istinbat al-Hukm via zahir al-nusus (textual ). In his history, Ibn Hazm was oriented towards the Zahiry madhhab, a madhhab which in the history of the development of Islamic thought was considered a madhhab whose opinions were very controversial. Likewise in the matter of istinbat al-hukm. They are called the Zahiry madhhab because they understand the passages of the Qur'an and Sunnah only based on zahir nusus alone and think that Islamic law can be answered only with zahir nusus without the need for ra'yu. This opinion is of course very contradictory to the opinion of the majority of ulama who (still) require the role of reason to answer the problems faced by Muslims. Ibn Hazm, as one of the Zahiry madhhab figures, the manhaj al-istinbat he holds is manhaj naqliyah, namely a method of istinbat that originates from the textual al-Nusus (al-Qur'an and as-Sunnah), not on ta'wil and neither on the legal ta'lil. This is because according to him, nusus is literal and external and fulfills human needs so that there is no need for ijtihad or the role of reason to establish a law. Furthermore, Ibn Hazm argued that the provisions of Sharia are found in the form of commands (al-amr) and prohibitions (al-nahy). If there is no clear text regarding an issue, it falls within the principles of ibahah that have been established in the qur’an